A genetic analysis of biological and economic efficiency of post-weaning feedlot performance in beef cattle - Van der Westhuizen, Robert Rolfe (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Agric))--University of Stellenbosch, 2005.